RECURRENT CLOSTRIDIOIDES DIFFICILE COLITIS – CASE REPORT - Georgievska, Dajana; Spasovska, Katerina; Vidinic, Ivan; Shopova, Zhaklina; Rangelov, Goran; Osmani, Arlinda; Poposki, Kostadin; Dimitrova, Emilija (Peytchinski Publishing Ltd., 2024)
Recurrent Clostridium difficile infection (rCDI) is usually defined as the reappearance of enteral symptoms 2-8 weeks after resolution of the initial episode with an appropriate therapy. Recurrence occurs in approximately 25% of patients within the first 30 days of the treatment. A 62-year-old female was initially hospitalized at our hospital within the intensive care unit (ICU) due to acute encephalitis and bilateral bronchopneumonia. Her comorbidities were diabetes mellitus and hypertension. She was treated with a combination of parenteral beta-lactam antibiotics for 35 days, acyclovir, probiotics, gastric suppression, and other supportive therapies. On the 18th hospital day, she developed diarrhea with liquid mucous green stools, prompting stool cultures and a C.difficile toxins test, which were negative and her condition stabilized spontaneously. A week later, she experienced a recurrence of enteral symptoms when stool cultures showed C.difficile positivity, but negative toxin tests. A colonoscopy was performed, revealing pseudomembranous pancolitis. Treatment continued with intravenous metronidazole and oral vancomycin for two weeks, alongside probiotics. This led to gradual improvement and normalization of stool consistency. Control cultures were C.difficile negative, and she was discharged after 49 days. Three weeks later, she complained of persistent watery stools and malaise, thus she was readmitted. New stool cultures confirmed C.difficile positivity with negative toxin tests. A repeat colonoscopy showed significant regression of pseudomembranous colitis and biopsy results indicated chronic nonspecific colitis. She was treated with probiotics, intravenous metronidazole for a week, and oral vancomycin. On first follow-up visit after three weeks, she returned asymptomatic with normal stools, and was advised to continue oral vancomycin, rifaximin, and probiotics. A second follow-up visit two weeks later confirmed normal stool characteristics. Prolonged use of antibiotics, extended hospital stays, advanced age, severe preexisting illness are significant risk factors for recurrent CDI. Prolonged oral vancomycin therapy has shown high efficacy in treatment of this serious condition.
Keywords: C.difficile; antibiotics; colitis; recurrence